2003
DOI: 10.1183/09031936.03.00061103
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between water vapour saturation of inhaled air and nasal patency

Abstract: The nasal cavity volume and the temperature of the nasal mucosa are considered to be the most important predictors of nasal conditioning. The aim of this study was to assess the relationship between the intranasal degree of water vapour saturation of inhaled air and nasal patency.Intranasal humidity values at different locations within the nasal cavity of 15 healthy subjects were compared to nasal airway resistance detected by active anterior rhinomanometry (AAR). Repeated measurements were carried out during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
2
29
0
1
Order By: Relevance
“…Signals of this device (TEMP‐2 and RH‐2) were compared with TEMP and RH signals that were simultaneously recorded directly in front of the patient's tracheal stoma (TEMP‐1 and RH‐1). Tracheal measurements of TEMP and humidity before and after application of an HME were performed similarly to measurements of nasal conditioning, as described previously by our working group 7–9 …”
Section: Methodsmentioning
confidence: 99%
“…Signals of this device (TEMP‐2 and RH‐2) were compared with TEMP and RH signals that were simultaneously recorded directly in front of the patient's tracheal stoma (TEMP‐1 and RH‐1). Tracheal measurements of TEMP and humidity before and after application of an HME were performed similarly to measurements of nasal conditioning, as described previously by our working group 7–9 …”
Section: Methodsmentioning
confidence: 99%
“…1 and 2A). This varying nasal mucosa temperature, which depends on local capillary blood temperature distribution, and the nasal cavity volume significantly contribute to the air‐conditioning process 30. On the other hand, just as chest wall dilation and contraction coincide with the displacements of definite zones within the body thermographic map (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In numerous studies, the experimental setup of our study was shown to be suitable for evaluating the humidifying and temperature-adjusting capacity of the respiratory tract [6,7,8]. Because of its easy handling the upper tracheal airway could be safely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The technical equipment for tracheal measurement of temperature and relative humidity (RH) was similar to the detection equipment for the measurement of nasal conditioning as described previously [6,7,8]. A thermocouple was connected to an RH sensor and placed into the upper part of the trachea.…”
Section: Methodsmentioning
confidence: 99%